The Corporation: The Pathological Pursuit of Profit and Power/Wealth by Stealth; Corporate Crime, Corporate Law and the Perversion of Democracy - Haley, Ella (Labour / Le Travail, 2005)
The article reviews the book, "Wealth by Stealth: Corporate Crime, Corporate Law and the Perversion of Democracy," by Harry Glasbeek.